Interaction Mechanisms of Cold Atmospheric Plasmas with HIV Capsid Protein by Reactive Molecular Dynamics Simulation - Ying Sun; Yang Chen; Yuantao Zhang (Molecules)
In recent years, plasma medicine has developed rapidly as a new interdisciplinary discipline. However, the key mechanisms of interactions between cold atmospheric plasma (CAP) and biological tissue are still in the exploration stage. In this study, by introducing the reactive molecular dynamics (MD) simulation, the capsid protein (CA) molecule of HIV was selected as the model to investigate the reaction process upon impact by reactive oxygen species (ROS) from CAP and protein molecules at the atomic level. The simulation results show that ground-state oxygen atoms can abstract hydrogen atoms from protein chains and break hydrogen bonds, leading to the destruction of the disulfide bonds, C–C bonds, and C–N bonds. Furthermore, the generation of alcohol-based groups resulting from the impact of ROS can alter the hydrophobicity of molecules and induce damage to the primary, secondary, and tertiary structures of proteins. The dosage effects on the reaction processes and products induced by CAP are also explored with varying numbers of ROS in the simulation box, and the influences on the broken C–H, N–H, and C–N bonds are discussed. In this study, the computational data suggest that severe damage can be caused to CA upon the impact of ROS by revealing the reaction processes and products.